Potentials of Social Media for HIV/AIDS Campaign among Nigerian Youths (2015)
Youths constitute a vibrant, critical resource input in the development process of any nation. It is, therefore, imperative that their health and wellbeing be safeguarded in the pursuit and sustenance of the socio-economic transformation of any society. With the unabated high prevalence of HIV and AIDS among this age cohort, communication campaigns must be restrategized, diversified and focused on effecting change in the behaviours that predispose young people to HIV infection. Providing youths with requisite information through social media has the potential of stemming the scourge of the virus. The paper critically examines the use of social media as a potentially veritable tool for campaigns aimed at combating the spread of HIV among Nigerian youths.